Jenis Ujaran Kebencian (Hate Speech) dalam Kolom Komentar Instagram Jokowi pada Masa PPKM: Analisis Linguistik Forensik - Deni Ferdiansa; Muhammad Darwis; Ikhwan M. Said (Jurnal Indonesia Sosial Teknologi, 2022)
Hate speech is often posted by someone on various social media, including Twitter and Facebook. Forms and functions can also vary. Hate speech found on social media Facebook in the form of provocation, incitement, insults, spreading false news and unpleasant behavior. Study this aims to know and explain types speech hatred in column Jokowi's Instagram comments during the PPKM period and knowing type speech the most dominant hatred in column Jokowi's Instagram comments during the PPKM period. Type study this is mixed (qualitative and qualitative). Method used _ in data collection, namely method watch use two technique, (1) technique tap with method catch screen (screenshot) and (2) technique read and write. At stage data analysis, the author uses a qualitative descriptive method to answer the first problem formulation, while the quantitative method is used to answer the second problem formulation. The population in this study, namely 50 data. The sampling technique used is the total sample. The entire population was used as the research sample. With a total of 21 examples of insults, 11 examples of incitement, 10 examples of defamation, and 8 examples of threats. Research results show that in column Jokowi's Instagram comments during the PPKM period are four types shape speech hatred. Shape that, that is humiliation, pollution name good, incitement, threats, and deeds no fun. As for the type speech the most dominant hatred spoken netizen is insults with a percentage of 42%.